If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(1 + -5v) = 54 (1 * -7 + -5v * -7) = 54 (-7 + 35v) = 54 Solving -7 + 35v = 54 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 35v = 54 + 7 Combine like terms: -7 + 7 = 0 0 + 35v = 54 + 7 35v = 54 + 7 Combine like terms: 54 + 7 = 61 35v = 61 Divide each side by '35'. v = 1.742857143 Simplifying v = 1.742857143
| 3(a-6)+4=-20+5a | | 6+5x-6=4x+8-x | | -10u+14=-20-11u+3u | | 7(2)-5(3)+4= | | -15+5n=n+5 | | (x^3+x^2+x+1)(18x-18)= | | 10-4x=3x-9x+40 | | x+6=4x^2 | | 12x-4=43 | | 180=4n+34 | | -10r+7=-2r+2-9r | | 1420=-680+420d | | yx=0.8 | | 180=5n+125 | | 10-m=9m-10 | | (x^3)-8(x^2)+11x+2=0 | | 13=-d+20 | | X^2-9x+20x=0 | | x^2-4x-2=5 | | 2a+8=a+12 | | -8w=-9-9w | | 7k-(5k-11)= | | 5m+7m=4m-12 | | 6x-4(6+5x)=-66 | | 4a-(2a+3)=-2(3-4a)+3 | | 14+12=15x+12x | | -9+6a-2=49 | | -9-8p+6p=p+9 | | 2p+q=3p+2q | | 6y-11x=15 | | 3a=49 | | N=Hmz |